1972
DOI: 10.1901/jeab.1972.18-181
|View full text |Cite
|
Sign up to set email alerts
|

Vicarious Conditioned Acceleration: Successful Observational Learning of an Aversive Pavlovian Stimulus Contingency

Abstract: Five rats (observers) were trained to avoid unsignalled shocks in a shuttlebox and then habituated to brief light presentations. They were next confined on an observation platform while another rat (model) received light-shock pairings in the opposite compartment. The observers were exposed only to the sight and sound of the model during classical conditioning and were not shocked themselves. Test presentations of the light during subsequent avoidance sessions produced response rate increases (vicarious condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
11
0
1

Year Published

1972
1972
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 17 publications
2
11
0
1
Order By: Relevance
“…The shuttle box produced considerably faster acquisition than normally obtained with the leverpress. Grossen & Bolles (1968) reported that shock rates in the shuttlebox were co n siderably lower than for the leverpress, and this has been confirmed by separate experience with both types of apparatus in this laboratory (Riess, 1970;Riess & Farrar, in press, b The purpose of the present experiments was to compare formally free operant avoidance in the shuttle box and Skinner box under otherwise identical parameters during both acquisition and terminal performance. Series 1200 modular pro grammi ng system with a 1231 control panel and a 1231-2 plug board.…”
supporting
confidence: 54%
See 1 more Smart Citation
“…The shuttle box produced considerably faster acquisition than normally obtained with the leverpress. Grossen & Bolles (1968) reported that shock rates in the shuttlebox were co n siderably lower than for the leverpress, and this has been confirmed by separate experience with both types of apparatus in this laboratory (Riess, 1970;Riess & Farrar, in press, b The purpose of the present experiments was to compare formally free operant avoidance in the shuttle box and Skinner box under otherwise identical parameters during both acquisition and terminal performance. Series 1200 modular pro grammi ng system with a 1231 control panel and a 1231-2 plug board.…”
supporting
confidence: 54%
“…The three shuttlebox Ss were holdovers from a long-term study (Riess, 1969) with 4 months of h urdle-cross avoidance experience und er parameters identical to those used in the present experiment. The three Skinner box Ss had about 5 months of leverpress experience at R-S = 20 (Riess, 1970).…”
mentioning
confidence: 99%
“…In doing so, it is important that verbal behavior not be given any causal or special sort of status. Observational learning certainly can, and does occur in the absence of verbal behavior, as is the case in animal research within this area (e.g., Biederman, Robertson, & Vanayan, 1986;Meyers, 1970;Reiss, 1972).…”
Section: Stimulus Substitutionmentioning
confidence: 95%
“…Concurrently, primatologists recognized signs of empathic sensitivities [16,17] and now neuroscientists, inspired by classic early behavioral studies [1820], are fashioning reliable simplified models to study the evolutionary roots of empathy (Box 1 and Figure 1)…”
Section: Introductionmentioning
confidence: 99%